Circulating oxidized LDL levels, current smoking and obesity in postmenopausal women. - Kassi, E; Dalamaga, M; Faviou, E; Hroussalas, G; Kazanis, K; Nounopoulos, Ch; Dionyssiou-Asteriou, A (Atherosclerosis, 2009)
OBJECTIVE: The aim of the present study was to estimate circulating oxidized low-density lipoprotein (oxLDL) levels in postmenopausal women and evaluate their association with obesity and smoking status. DESIGN AND METHODS: The study included 135 postmenopausal women aged 52-75 years. Forty of them were overweight (BMI 32.4+/-6.4) and non-smokers (Group A), 40 non-overweight (BMI 22.6+/-1.8) and smokers (Group B) and 55 non-overweight (BMI 23.5+/-1.4) and non-smokers (Group C). oxLDL and antibodies against them (anti-oxLDL) were measured using ELISA. Serum total cholesterol, LDL, HDL and triglycerides were measured in an automated analyzer. RESULTS: Total cholesterol, LDL, HDL and oxLDL serum levels were significantly elevated in Group A as compared to Group B or C, as well as oxLDL in Group B in comparison to Group C (p<0.001). Triglycerides and anti-oxLDL were increased in Group A in comparison to Group C (p=0.043 and 0.023). Total cholesterol, LDL, triglycerides and anti-oxLDL did not differ between Groups B and C, while HDL was decreased in Group B as compared to Group C (p<0.001). A significant positive correlation was found between oxLDL and LDL in Group A (r=0.53, p<0.001) as well as in Group C (r=0.955, p<or=0.001) and a negative one between oxLDL and HDL in Group C (r=-0.933, p<0.001). Regression analysis revealed that obesity was a stronger predictor of LDL oxidation than smoking. CONCLUSIONS: Postmenopausal obesity is involved in the process of LDL oxidation and appears to be a stronger predictor of LDL oxidation than smoking. Future studies are needed to confirm these associations.
Keywords: Aged; Body Mass Index; Female; Humans; Lipoproteins, LDL; Middle Aged; Obesity; POSTMENOPAUSE; Regression Analysis; Risk Factors; Smoking; Tobacco Use Disorder